Langmuir Turbulence Effects on Coastal Surface Waves - Jiehua Wu; Peng Wang (Journal of Marine Science and Engineering)
Langmuir turbulence is widely recognized for enhancing upper-ocean mixing and altering current dynamics; however, its influence on surface wave characteristics remains insufficiently understood. Due to the difficulty in resolving Langmuir turbulence in ocean models, its effect is usually parameterized. In this study, we implement a Langmuir turbulence parameterization into a coupled wave–circulation model and use it to investigate the effects of Langmuir turbulence on the evolution of surface waves under upwelling-favorable wind conditions over an idealized continental shelf. The results indicate that Langmuir turbulence significantly modifies the spatial distribution and gradients of wave height, primarily through the modulation of current-induced wave refraction. Specifically, Langmuir turbulence suppresses coastal currents and associated vorticity, thereby weakening the impact of current-induced wave refraction. This leads to diminished alongshore wavenumber gradients and weakens the focusing of wave energy, which, in turn, reduces alongshore wave height gradients. Furthermore, this attenuation of wave height gradients by Langmuir turbulence remains robust across different wave–wind misalignment angles. These findings provide evidence of Langmuir turbulence’s role in wave energy redistribution and underscore the importance of incorporating its dynamics into coupled wave–current modeling frameworks.